Penyuluhan Kepada Masyarakat Desa Pakuncen Kecamatan Bojonegara dengan tema “Peluang Usaha Pengembangan Bebek Peking Pedaging,Telur DOD/Day Old Duck” dan Aspek Legalitas Merek Dagang - Eli Apud Saepudin; Sulkiah Hendrawati; Sherlinda (Jurnal Transformasi Pendidikan Indonesia, 2024)
The aspect of trademark legality in the sale of Peking Duck is a superior duck to be developed, this duck is not from Indonesia, but the habitat and ecosystem in Indonesia are very suitable for the development of Peking duck. Therefore, let's pick up this good opportunity to be used as a promising business opportunity, hopefully with perseverance and hard work accompanied by prayer, this valuable opportunity can be utilized as well as possible. Hopefully, our standard of living and income will increase. Qualification of the types of results from peking duck cultivation, are in the form of; eggs, DOD (day old duck), and meat. The demand for peking ducklings (DOD) is quite high but not matched by adequate egg supply. The need for peking duck meat consumption in some major cities in Indonesia is also quite high.